Dooryard Fruit Varieties - J. G. Williamson; J. H. Crane; T. Vashisth; Ali Sarkhosh (EDIS)
Considerations for selecting proper fruit species and cultivars for north, central, and south Florida are discussed including chilling requirement, cold hardiness, and warm weather adaptability. Varieties of temperate, subtropical, and tropical fruit crops that are suited for noncommercial home gardener production are provided. Minor revision. https://edis.ifas.ufl.edu/mg248